Experimental and Modeling Study of Kinetics for Hydrate Decomposition Induced by Depressurization in a Porous Medium - Ruan, Xuke; Xu, Chun-Gang; Yan, Ke-Feng; Li, Xiao-Sen (Frontiers in Energy Research, 2021)
The hydrate decomposition kinetics is a key factor for the gas production from hydrate-saturated porous media. Meanwhile, it’s also related to other factors. Among them, the permeability and hydrate dissociation surface area on hydrate dissociation kinetics have been studied experimentally and numerically in this work. First, the permeability to water was experimentally determined at different hydrate saturations (0%, 10%, 17%, 21%, 34%, 40.5%, and 48.75%) in hydrate-bearing porous media. By the comparison of permeability results from the experimental measurements and theoretical calculations with the empirical permeability models, it was found that for the lower hydrate saturations (less than 40%), the experimental results of water permeability are closer to the predicted values of the Grain-Coating permeability model, while for the hydrate saturation above 40%, the tendencies of hydrate accumulation in porous media are quite consistent with the pore-filling hydrate habits. A developed 2D core-scale numerical code, which incorporates the models for permeability and hydrate dissociation surface area along with the hydrate accumulation habits in porous media, was used to investigate the kinetics of hydrate dissociation by depressurization, and a “shrinking-core” hydrate dissociation driven by the radial heat transfer was found in the numerical simulations of hydrate dissociation induced by depressurization in core-scale porous media. The numerical results indicate that the gas production from hydrates in porous media has a strong dependence on the permeability and hydrate dissociation surface area. Meanwhile, the simulation shows that the controlling factor for the dissociation kinetics of hydrate switches from permeability to hydrate dissociation surface area depending on the hydrate saturation and hydrate accumulation habit in porous media.